Reflection - an effective strategy for outcome-based learning in basic medical sciences - Uzma Mussarat; Zainub, Abeerah; Hanif, Rabia; Ayub, Sadaf; Naureen, Fakhra; Inam, Tahira (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the role of guided reflection for improved learning outcomes in students of basic dental sciences. Method: The quasi-experimental comparative educational study was conducted at the Islamic International Dental College, Islamabad, Pakistan, from May to September 2019, and comprised second-year undergraduate students in the Basic Medical Sciences curriculum for Microbiology. The subjects were arbitrarily divided into Group-1, which was exposed to guided reflection, and Group-2, which was not asked to reflect on the lectures. Post-intervention, a test of 30 multiple choice questions on the selected topics was conducted to compare the level of learning between the groups. After three weeks, the same activity was repeated with the same groups, but with different topics of lectures. Data was analysed using SPSS 21. Results: Of the total 75 students, there were 28 female and 9 male students in Group-1 (Reflectors), 29 female and 9 male students in Group-2 (Non-Reflectors). Overall, there were 18 male and 57 female students. The overall mean age was 20 years The difference between the groups after the first session was not significant (p>0.05). After session 2, Group-1 score was significantly better than that of Group-2 (p<0.05). Conclusion: Reflective practices on teaching sessions at the end of lectures proved to be an effective strategy to achieve outcome-based learning.